CURRICULUM MATERIALS AND AUXULIARIES USED IN THE STUDY OF GEOGRAPHY OF THE LOCAL HORIZON (PANGEEA, 2025)
ABSTRACT: The local horizon is the area where the locality we live in is found, including all the features of the topography and the natural scenery. The teaching materials belonging to the field of geography ensure a fully equipped study rooms, being especially useful in Geography lessons with the theme Local Horizon: mural plans, locality plans, QGIS maps made by the teacher, atlases and three-dimensional models, and so on. A curricular auxiliary used in the study of geography of local horizon, both in secondary and high school, may be the course support for the optional "Geography of the Local Horizon". It may include elements of physical, human and economic geography.
Keywords: local horizon; premises; devolopment; curricular auxiliaries; methods; analysis; synthesis; Geography of the local horizon